Structural Studies of Klebsiella pneumoniae Fosfomycin-Resistance Protein and Its Application for the Development of an Optical Biosensor for Fosfomycin Determination - Varotsou, Christina (Switzerland, 2025)
Fosfomycin-resistance proteins (FosAs) are dimeric metal-dependent glutathione transferases that conjugate the antibiotic fosfomycin (Fos) to the tripeptide glutathione (γ-Glu-Cys-Gly, GSH), rendering it inactive. In the present study, we reported a comparative analysis of the functional features of two FosAs from Pseudomonas aeruginosa (FosAPA) and Klebsiella pneumoniae (FosAKP). The coding sequences of the enzymes were cloned into a T7 expression vector, and soluble active enzymes were expressed in E. coli. FosAKP displayed higher activity and was selected for further studies. The crystal structure of the dimeric FosAKP was determined via X-ray crystallography at 1.48 Å resolution. Fos and tartrate (Tar) were found bound in the active site of the first and second molecules of the dimer, respectively. The binding of Tar to the active site caused slight rearrangements in the structure and dynamics of the enzyme, acting as a weak inhibitor of Fos binding. Differential scanning fluorimetry (DSF) was used to measure the thermal stability of FosAKP under different conditions, allowing for the selection of a suitable buffer to maximize enzyme operational stability. FosAKP displays absolute specificity towards Fos; therefore, this enzyme was exploited for the development of an enzyme-based colorimetric biosensor. FosAKP was tethered at the bottom of a plastic cuvette using glutaraldehyde chemistry to develop a simple colorimetric method for the determination of Fos in drinking water and animal plasma.